Serum ferritin levels in children of simple febrile seizures in tertiary institute - Mahajan, Anirudh; Rasool, Ifra; Gupta, Ravinder K.; Sharma, Harsh Vardhan; Mehta, Abhijay (International Journal of Contemporary Pediatrics, 2024)
Background: Seizure onset is impacted by a number of variables, including genetics, diet, geography, concurrent illnesses, metabolic state, history of head trauma, and blood levels of particular minerals. Due to the fact that iron is required for the proper functioning of a number of enzymes and neurotransmitters in the central nervous system, low blood ferritin levels may lower the seizure threshold. The aim of the study was to determine the association between serum ferritin levels and simple febrile seizures. Methods: The present observational study was conducted in department of pediatrics of a tertiary institute and included a total of 200 study subjects who visited to pediatric OPD/emergency room with febrile illness. The data was collected with the help of a structured clinical proforma. The collected data was recorded in Microsoft Excel sheet and statistical analysis was done with the help of SPSS version 21.0. Results: In our study, the maximum number of the study subjects were between 13 and 24 months (35%) with male to female ratio 1.2:1. In patients with simple febrile seizure the mean Hb level was 9.1±1.4 gm/dl, the mean MCV was 72.6±7.4 f1, mean MCH was 23.73±3.2 pg and mean serum ferritin was 13.4±9.5 ng/ml as compared to those patients with febrile illness without seizure the mean Hb level was 11.5±1.2 gm/dl, mean MCV was 82.1±5.5 f1, mean MCH was 29.6±2.9 pg and mean serum ferritin was 33.6±20.2 ng/ml. Conclusions: It is concluded that the low serum ferritin level is a risk factor of simple febrile seizure.